Initiation of antiretroviral therapy based on the 2015 WHO guidelines. (28th November 2016) - Kuznik, Andreas; Iliyasu, Garba; Habib, Abdulrazaq G.; Musa, Baba M.; Kambugu, Andrew; Lamorde, Mohammed
Abstract : Objective: In 2015, the WHO recommended initiation of antiretroviral therapy (ART) in all HIV-positive patients regardless of CD4 + cell count. We evaluated the cost-effectiveness of immediate versus deferred ART initiation among patients with CD4 + cell counts exceeding 500cells/μl in four resource-limited countries (South Africa, Nigeria, Uganda, and India). Design: A 5-year Markov model with annual cycles, including patients at CD4 + cell counts more than 500 cells/μl initiating ART or deferring therapy until historic ART initiation criteria of CD4 + cell counts more than 350 cells/μl were met. Methods: The incidence of opportunistic infections, malignancies, cardiovascular disease, unscheduled hospitalizations, and death, were informed by the START trial results. Risk of HIV transmission was obtained from a systematic review. Disability weights were based on published literature. Cost inputs were inflated to 2014 US dollars and based on local sources. Results were expressed in cost per disability-adjusted life years averted and measured against WHO cost-effectiveness thresholds. Results: Immediate initiation of ART is associated with a cost per disability-adjusted life years averted of −317 [95% confidence interval (CI): −796–817] in South Africa; −507 (95% CI: −765–837) in Nigeria; −136 (−382–459) in Uganda; and −78 (−256–374) in India. The results are largely driven by the impact of ART on reducing the risk of new HIV transmissions. Conclusions: In HIV-positive patients with CD4 + counts above 500 cells/μl in the four studied countries, immediate initiation of ART versus deferred therapy until historic eligibility criteria are met is cost-effective and likely even cost-saving over time. Abstract : Supplemental Digital Content is available in the text